Alterações epigenéticas e do número de cópias do gene SFN em carcinomas mamários - Brotto, Danielle Barbosa [UNESP] (2014)
The SFN gene (Stratifin; 14-3-3 sigma) plays roles as a tumor suppressor gene and its expression is induced in response to DNA damage by disabling the cell cycle arrest at the G2/M checkpoint. Inactivation or down-regulation of gene expression levels has been generally attributed to the hypermethylation of its CpG island, identified as a common mechanism in a variety of human cancers, also associated to treatment response. The aim of the present study was to characterize epigenetics and genetics alterations of the SFN gene in primary breast cancer and to investigate the relationship with clinical and histopatological variables. In addition, cell lines derived from normal breast and breast cancer tissues, were employed to identify the effect of copy number dosage and DNA methylation pattern in gene expression, besides the study of combined response to 5-Aza-dC (5-Aza-2'-Deoxycytidine) and radiation exposure on cell survival. After sodium bisulfite modification, the DNA methylation pattern was determined by Methylation-Specific Polymerase Chain Reaction (MS-PCR) in a series of 84 Breast cancer samples (76 infiltrating ductal carcinomas, 5 infiltrating lobular, 1 metaplasic, 1 apocrine and 1 papillary) as well as in a panel of 20 human cell lines (3 derived from normal breast and 17 from breast cancer). SFN copy number was performed using relative quantification, by qPCR (quantitative Polimerase Chain Reaction) in 82 samples. Transcript levels were evaluated by RT-qPCR within a selection of 8 cell lines, based on DNA methylation, SFN copy number dosage and p53 status. Ionizing radiation effect was studied through MTT (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide) assay, by using a single dose of 4 Gy at different time intervals (12, 24, 48 and 72h) in tree cell lines (T47D, MDA-MB-231 e MDA-MB-436) treated or not with 5-Aza-dC. SFN methylation was observed in 79% of primary breast cancer, while copy number alterations ...